Reassessing Al-Khwarizmi’s Intellectual Legacy in the Era of Industrial Revolution 5.0 - Andayani, Siti; Ridwan, Ridwan; Susetyo, Budi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to examine the intellectual relevance of Al-Khwarizmi’s scientific legacy within the framework of Industrial Revolution 5.0, particularly in relation to the development of artificial intelligence, machine learning, digital computation, and the human-centered technology paradigm. Employing a qualitative approach with a library research design, the study integrates a historical-philosophical and conceptual analysis framework to explore the epistemological continuity between classical Islamic scientific thought and contemporary technological systems. Data were collected through documentary research from primary sources, including Al-Khwarizmi’s seminal works such as Al-Kitab al-Mukhtasar fi Hisab al-Jabr wa al-Muqabalah, as well as secondary literature encompassing peer-reviewed journals, books, and scholarly discussions on Industrial Revolution 5.0, AI ethics, and Islamic philosophy of science, particularly the works of Syed Muhammad Naquib al-Attas and Ismail Raji al-Faruqi. The data were analyzed using qualitative content analysis and thematic coding to identify key conceptual patterns such as algorithmic reasoning, rational inquiry, knowledge integration, and ethical epistemology, followed by historical-interpretative and comparative analysis to trace their transformation into modern computational paradigms. The findings reveal that Al-Khwarizmi’s contributions to algebra, algorithmic thinking, and systematic reasoning constitute a foundational epistemological infrastructure for contemporary digital technologies, including artificial intelligence systems, predictive analytics, and automated decision-making processes. His intellectual legacy shows a strong alignment with the human-centered orientation of Industrial Revolution 5.0, as it inherently emphasizes rationality, structured inquiry, and the pursuit of human welfare. When integrated with the ethical and philosophical Al-Attas and Al-Faruqi, Al-Khwarizmi’s thought provides a comprehensive framework that bridges scientific innovation and moral responsibility, showing the necessity of embedding ethical governance within modern technological development.